Organic metal complexes based on zoledronate–calcium: a potential pDNA delivery system. Issue 8 (3rd February 2017) - Li, Wenpan; Xin, Xiu; Jing, Shasha; Zhang, Xirui; Chen, Kang; Chen, Dawei; Hu, Haiyang
Abstract : Organic metal complexes as a type of hybrid materials have been used for gene delivery. Abstract : Organic metal complexes as a type of hybrid materials have been used for gene delivery. In the present study, a metal organic complex of zoledronate–calcium (CaZol) was prepared for transporting pDNA. Then, the effects of different molar ratios of Ca 2+ to Zol (Ca/Zol) on the formulation characteristics were investigated. The results showed that the CaZol/pDNA complexes generated small particles and efficiently encapsulated pDNA when the Ca/Zol ratio was 30. In addition, CaZol complexes could protect pDNA from being degraded by the serum protein since pH-sensitive CaZol exhibited high stability in the physiological environment (pH 7.4), whereas the encapsulated pDNA could be released in a weakly acidic environment (pH 5.5). Moreover, the complex had better cellular uptake efficiency and desired gene expression efficiency in vitro and in vivo . Overall, these results indicated that CaZol, as a potential nanocarrier, was suitable for pDNA delivery.